(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to determine the prevalence and severity of malocclusion among adolescents with intellectual disabilities aged 12–18 years in Da Nang, and to assess its association with bad oral habits (including tongue thrusting, mouth breathing, and thumb sucking). Methods: A cross-sectional study was conducted involving 82 participants aged 12–18 years from three special education centers (April - June 2025). The Dental Aesthetic Index (DAI) was used to evaluate malocclusion severity. Multivariable linear regression analyses were applied to examine associations between oral habits and malocclusion. Results: The mean DAI score was 34.44 ± 13.32 (Median: 33, quartiles: 26.25-39.75). A total of 70.7% of participants exhibited at least one bad oral habit with tongue thrusting being the most common (48.8%). The proportion of children requiring orthodontic treatment (DAI ≥ 26) was 76.8%, with the highest proportion (30.5%, 95% CI: 21.1–41.8) classified as having very severe or handicapping malocclusion (DAI ≥ 36). There was a statistically significant association between tongue thrusting and an increase in the mean DAI score (B=6,97; KTC 95%: 1,17 – 12,77; p=0,019). No association was found between mouth breathing, thumb sucking habits, and the average DAI score. Conclusions: The prevalence of malocclusion in intellectually disabled children aged 12 - 18 was high. Specifically, severe malocclusion accounted for a high proportion. Notably, tongue thrusting was associated with an increase in malocclusion severity.